Microglia Gone Awry: Linking Immunometabolism to Neurodegeneration - Afridi, Ruqayya; Lee, Won-Ha; Suk, Kyoungho (Frontiers in Cellular Neuroscience, 2020)
Age-related chronic inflammatory activation of microglia and their dysfunction are observed in many neurodegenerative diseases, and the potential contributions of these dysfunctional cells to neurodegeneration have been demonstrated recently. The housekeeping and defensive functions of microglia, such as surveying brain parenchyma and phagocytosis of neuronal debris after injury, are important for brain homeostasis and immunity. During neurodegenerative diseases, loss of these functions can promote disease pathology by producing proinflammatory cytokines and increasing oxidative stress, which can exaggerate ongoing neuroinflammation. A recent surge in microglial research has unraveled myriads of microglial phenotypes associated with aging and neurodegenerative diseases, in addition to conventional M1/M2 paradigm. Each of these phenotypes can be characterized by distinct transcriptional profiles as well as altered metabolism, migration, and phagocytosis characteristics. Mutations in Trem2 and Grn are associated with various neurodegenerative diseases, and these genes are dysregulated in majority of recently identified microglial phenotypes. These genes act as checkpoint regulators and maintain microglial inflammatory fitness, principally through metabolic modulation. Dysfunctional microglia typically show mitochondrial deficits, glycolysis elevation, and lipid droplet accumulation, which results in reduced migration and phagocytosis and increased proinflammatory cytokine secretion and reactive oxygen species release. In this mini-review, we discuss the existing data regarding metabolic perturbations in dysfunctional microglia and their documented associations with neurodegeneration, highlighting how aging-induced chronic microglial activation alters microglial bioenergetics, leading to impaired homeostatic and housekeeping functions. Dysfunctional microglia initiate or exacerbate neurodegeneration, and key pathways involved in the dysfunctional processes, including metabolism, may represent potential intervention targets for correcting imbalances.